Revitalizing TiO2 photoelectrocathodes for integrated CO2-to-dimethyl carbonate electrosynthesis via Ag 4d–O 2p orbital hybridization and dual-scale design - Youjia Wang; Yuxin Tian; Bochen Tian; Wenchao Wang; Xin Ma; Yanfeng Dong; Yansheng Liu; Junwei Hou (Chemical Engineering Journal, 2026)

Trajectory data–driven modeling and optimization of urban freight charging networks - Yanchao Lu; Runsheng Zhang; Ruoxuan Wang; Bochen Fu; Kaiming Lu; Pengfei Fan; Lei Yu; Guohua Song (Transportation Research Part D: Transport and Environment, 2026)

Wave propagation model considering cross-scale attenuation mechanism and pressure influence - Fansheng Xiong; Jiawei Liu; Zhenwei Guo; Bochen Wang; Jianxin Liu (Acta Geophysica, 2026)

Planting 2D perovskite seeds to prepare mixed-dimensional perovskite solar cells with high stability - Sijia Guo; Bochen Liu; Shunli Peng; Tianhao Li; Yangyang Wang; Xianyu Deng (Chemical Engineering Journal, 2026)

Identifying reservoir landslide deformation evolution stages with time series InSAR: application to the Xinpu landslide in China’s three Gorges region - Wu Zhu; Qian He; Jing Wu; Yue Wang; Zhenhong Li; Jiewei Zhan; Bochen Zhang (Journal of Hydrology, 2025)

Dual regulation of interfacial proton transport and alloy electronic structure in Cu-In-(COOH)CNTs catalysts for selective CO2 electroreduction - Youjia Wang; Bochen Tian; Jia Zhuo; Xin Ma; Yuxin Tian; Wenchao Wang; Yansheng Liu; Junwei Hou (Journal of Environmental Chemical Engineering, 2025)

Combined effects of micro/nanoplastics and ZnO nanoparticles on lactuca sativa seedlings under varied lighting - Xuancheng Yuan; Bochen Zhang; Fan Zhang; Zhuang Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Ca(OH)2 nanosheets fabricated by carbide residue for effective dry desulfurization - Panpan Wang; Meiyu Shi; Bochen Zhao; Yuan Shu; Qiang Niu; Pengfei Zhang (Journal of Environmental Chemical Engineering, 2025)

Constructing efficient PVDF-HFP-based intercalated composite solid electrolytes via competitive solvation structures for rechargeable lithium metal batteries - Yutong Jing; Shen Liu; Cheng Li; Qiang Lv; Daming Liu; Manxing Huo; Bochen Wu; Siyuan Liu; Yuhang Zhang; Mingyu Yin; Zhipeng He; Dianlong Wang; et al. (Chemical Engineering Journal, 2025)

Application and progress of smart hydrogel microspheres for regulating oxidative stress in osteoarthritis - Jinping Chen; Chengcheng Du; Bochen Tang; Jiacheng Liu; Pengcheng Xiao; Xingkuan Wang; Zhong Alan Li; Wei Huang; Yiting Lei (Chemical Engineering Journal, 2025)

Evaluation of InSAR applicability using a new multi-index and optical imagery: A case study in the Guangdong-Hong Kong-Macao greater bay area, China - Zhijie Zhang; Songbo Wu; Chaoying Zhao; Guoqiang Shi; Xiaoli Ding; Bochen Zhang; Ziyuan Li; Yan Wang; Zhong Lu (Remote Sensing Applications: Society and Environment, 2025)

Determination of multi-residue pesticides in dairy products using single-step emulsification/demulsification clean-up strategy combined with low-pressure gas chromatography-tandem mass spectrometry - Hao Peng; Hongmei Li; Xianjiang Li; Bochen Wei; Zhenxia Du; Guoying Wei; Sheng Wang (Food Chemistry, 2024)

Multi-Module Fusion Model for Submarine Pipeline Identification Based on YOLOv5 - Bochen Duan; Shengping Wang; Changlong Luo; Zhigao Chen (Journal of Marine Science and Engineering, 2024)
In recent years, the surge in marine activities has increased the frequency of submarine pipeline failures. Detecting and identifying the buried conditions of submarine pipelines has become critical. Sub-bottom profilers (SBPs) are widely employed for pipeline detection, yet manual data interpretation hampers efficiency. The present study proposes an automated detection method for submarine pipelines using deep learning models. The approach enhances the YOLOv5s model by integrating Squeeze and Excitation Networks (SE-Net) and S2-MLPv2 attention modules into the backbone network structure. The Slicing Aided Hyper Inference (SAHI) module is subsequently introduced to recognize original large-image data. Experimental results conducted in the Yellow Sea region demonstrate that the refined model achieves a precision of 82.5%, recall of 99.2%, and harmonic mean (F1 score) of 90.0% on actual submarine pipeline data detected using an SBP. These results demonstrate the efficiency of the proposed method and applicability in real-world scenarios.

Safety-critical control for autonomous underwater vehicles with unknown disturbance using function approximator - Chenggang Wang; Bochen Li; Lei Song; Xuanmin Du; Xinping Guan (Ocean Engineering, 2023)

Correction to: Study on the resource utilization of high fluorine-containing organic waste through fluidized incineration - Wenhan Li; Zengyi Ma; Jianhua Yan; Qianming Huang; Xingjian Wen; Zian Zhai; Bochen Huang; Shuang Wang; Yongqiang Chen (Waste Disposal & Sustainable Energy, 2023)

Lateral behavior of monopiles considering the effects of sand subsidence and densification under lateral cyclic loading - Yang Wang; Mingxing Zhu; Weiming Gong; Guoliang Dai; Hongqian Lu; Bochen Wang (Marine Georesources & Geotechnology, 2022)

Study on the resource utilization of high fluorine-containing organic waste through fluidized incineration - Wenhan Li; Zengyi Ma; Jianhua Yan; Qianming Huang; Xingjian Wen; Zian Zhai; Bochen Huang; Shuang Wang; Yongqiang Chen (Waste Disposal & Sustainable Energy, 2022)